2d-Page and Bioinformatics Analysis of Diseased and Non- Diseased Piper nigrum - Ahmat Amrin, Abdul Mutalib (Universiti Malaysia Sarawak (UNIMAS), 2018)
Piper nigrum have been used widely documented in many sectors such as food and medicine industry. Plant as a role model shows various strategy to survive under different pressure. However, the information on proteins associate with the properties and biological process under environmental stress for P. nigrum are limited. The main aim for this study was to extract protein and differentiate the protein expressed through in silco analysis from diseased and non-diseased steam and root of P. nigrum. The study was iniatiated by extracting protein by using imidazole-tca precipitation method. The protein was quatified by using Bradford assay and further diffrentiated by its isoelectric point in 2D PAGE. The results were analyzed by the aid of Delta2D software and perform direct differentiation through the statistics. The protein content within each plant vary slightly as it were dependent on the pressure applied to the plant. A distinct spot difference expressed by the two different condition of the plant shows some protein to be suppressed while some protein were expressed more. The study provides an initial insight into the P. nigrum proteome and its response to disease.